Реверсія уявного: інтертекстуальність персоносфери як чинник жанрової метаморфності роману Кліффорда Саймака «Резервація гоблінів» - Paranyuk, Dan (ANADISS, 2018)
Based on Jean Baudrillard’s methodology on the beginning of the era of hyperreality as the “world of simulation”, the article under discussion substantiates the expansion of science fiction horizons by means of “reversing the imaginary”. The latter notion is mostly marked with the inter-penetration of fictional worlds, which are genealogically revealed only in their connection with new genre forms. Particular emphasis in the “hyperreal indifference” of science fiction narratives has been laidonintertextual ties. The article updates the issue of intertextual potential of the personosphere of science fiction and fantasy, which, according to TzvetanTodorov, presupposes “reader’s active integration into the world of characters”. In this way, the specifics of including the “fantasy” characters of Shakespeare’s plays into the intertextual space of science fiction has been analyzed
Keywords: science fiction, intertextual personosphere, genre metamorphicality, William Shakespeare, Clifford Simak.